2008
DOI: 10.1002/ange.200802002
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Oxazaborolidinium‐Catalyzed Diels–Alder Reactions without CH⋅⋅⋅⋅O Hydrogen Bonding

Abstract: The oxazaborolidine Diels-Alder (DA) precatalysts first introduced by Corey et al. in 2002 [1] are remarkable for several reasons. The derived oxazaborolidinium cations, for example 1 a·HNTf 2 or 1 a·MX n (formed by exposure to either Brønsted [1][2][3] or Lewis [4] acids, Scheme 1), are active catalysts for enantioselective cycloadditions involving a broad range of dienes and dienophiles. [1][2][3][4][5][6][7][8][9][10][11][12] Perhaps the most significant quality of this family of Lewis acid (LA) catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…It was also demonstrated for the first time that enantioselective Diels-Alder reactions with the parent [3]dendralene (11) are possible. Thus, through the application of a modified [28,202] version of Coreys oxazaborolidinium catalyst, 243, the mono-cycloaddition of methyl acrylate to [3]dendralene (11) produced monoadduct 239 in a respectable 86 % yield and 92 % ee. It was demonstrated that the presence of a bicyclic framework is not necessary for good anti-p-diastereofacial stereoselectivity (cf.…”
Section: Methodsmentioning
confidence: 99%
“…It was also demonstrated for the first time that enantioselective Diels-Alder reactions with the parent [3]dendralene (11) are possible. Thus, through the application of a modified [28,202] version of Coreys oxazaborolidinium catalyst, 243, the mono-cycloaddition of methyl acrylate to [3]dendralene (11) produced monoadduct 239 in a respectable 86 % yield and 92 % ee. It was demonstrated that the presence of a bicyclic framework is not necessary for good anti-p-diastereofacial stereoselectivity (cf.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are instances in which a different transition state structure is favored because of other steric or electronic interactions. 44 Therefore, detailed analysis for each individual reaction and substrate seems to be necessary. The role of aluminum bromide in the thermal catalysis of 1,3,2-oxazaborolidines was investigated through computational studies by Sakata and Fujimoto.…”
Section: Binding Modes and Computational Studiesmentioning
confidence: 99%
“…In diesen Untersuchungen wurde zudem erstmals gezeigt, dass mit dem Stammkohlenwasserstoff 11 auch enantioselektive Diels-Alder-Additionen mçglich sind. Beispielsweise ließ sich durch Nutzung einer modifizierten Form [28,202] [53,54,156] Erst 1992 identifizierten Trahanovsky und Koeplinger als Hauptprodukt der thermischen Dimerisierung das Diels-Alder-Produkt 242. [156] Daten zur Geschwindigkeit der Dimerisierung von 11 als reiner Flüssigkeit bei Raumtemperatur wurden gar erst 2010 ermittelt.…”
Section: Dien-transmissive Diels-alder-reaktionen Von Dendralenenunclassified